An in Vitro Effectiveness and Evaluation of Sodium Hypochlorite for Orthodontic Buccal Tube Disinfection - Muhamat Muhtar S. Abdurrohman; Dandy Andrea Rainanda; Anggun Feranisa; Ade Ismail Abdul Kodir (Universitas Muhammadiyah Yogyakarta, 2023)
Contamination of fixed orthodontic components caused by non-compliance with hygiene both during the manufacturing and packaging processes can cause cross-infection. Although the literature has demonstrated the need for sterilization or disinfection of fixed orthodontic components prior to insertion in the oral cavity, these are still not widely used in orthodontic practice. This study aims to evaluate bacterial contamination in vitro and the disinfection effect of 0.5% sodium hypochlorite on orthodontic buccal tubes. A total of 12 roth type 1 Molar buccal tubes with slots of 0.020 and still well sealed in the packaging were divided into three groups: group 1 chlorhexidine 2% (n=4), group 2 distilled water (n=4) as control, and group 3 sodium hypochlorite 0.5% (n=4) as treatment. Microbiological and biochemical tests were carried out on the three groups of first molars to detect any bacterial contamination. The buccal tube showed that it was contaminated with bacteria and then disinfected using a 2% chlorhexidine solution, distilled water and 0.5% sodium hypochlorite. Bacterial contamination was detected in all control and treatment groups. The treatment group with 0.5% sodium hypochlorite disinfection showed optimal decontamination (p 0.05) compared to the negative control group. Therefore, In vitro sodium hypochlorite 0.5% had the effect of reducing bacterial contamination of the buccal tube Roth type 1 molar with 0.020 slots.